2017
DOI: 10.1177/1090198116687713
|View full text |Cite
|
Sign up to set email alerts
|

Individual- and School-Level Factors Related to School-Based Salad Bar Use Among Children and Adolescents

Abstract: Little research has examined factors related to school-based SB use. These findings suggest recommendations that may help improve student use of SBs. For example, increasing the promotion of SB, particularly in secondary schools, might encourage their use among students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…Since these studies used self- and parentally-reported measures of food intake, there is potential for response bias as fruit and vegetable intake is a socially desirable behavior. However, studies using more objective assessment methods in schools have also observed that female students are more likely to consume from a salad bar than males [38,39]. The alignment with observational data strengthens the findings from questionnaires, suggesting that female children tend to consume more fruits and vegetables than males.…”
Section: Evidence For Sex Differences In Children’s Eating Behaviorsupporting
confidence: 61%
“…Since these studies used self- and parentally-reported measures of food intake, there is potential for response bias as fruit and vegetable intake is a socially desirable behavior. However, studies using more objective assessment methods in schools have also observed that female students are more likely to consume from a salad bar than males [38,39]. The alignment with observational data strengthens the findings from questionnaires, suggesting that female children tend to consume more fruits and vegetables than males.…”
Section: Evidence For Sex Differences In Children’s Eating Behaviorsupporting
confidence: 61%
“…Since these studies used self-and parentally-reported measures of food intake, there is potential for response bias as fruit and vegetable intake is a socially desirable behavior. However, studies that have used more objective assessment methods in schools have also observed that female students are more likely to consume from a salad bar than males 49,50 .The alignment with observational data strengthens the findings from questionnaires, suggesting that female children tend to consume more fruits and vegetables than males.…”
Section: Sex Differences In Food Intakesupporting
confidence: 62%
“…Notably, it was not clear in both studies whether the observed changes were due to the simple increases in availability, due to an increase in stated personal restraint (Lowe et al, ) based on energy‐density‐information, due to increased knowledge about healthy consumption (Franco et al, ) or due to a combination of multiple effects. Support for multiple effects may also be drawn from results of Spruance, Myers, O'Mally, Rose, and Johnson () who found that for children, a combination of school‐level factors and personal factors were associated with the odds of using a salad bar in the school canteen.…”
Section: Resultsmentioning
confidence: 99%